Karate basics - Rielly, Robin L. (North Clarendon, VT Tuttle Publishing, 2003)
Karate Basics teaches you all the fundamentals of this ancient martial art form in a clear and easy-to-understand manner! This book contains the following vital information: the origins of karate-its philosophy, history, and different schools; how to find a teacher and a class that are right for you; getting ready for your first class-what actually happens in a karate class?;The essential elements-stances, blocks, thrusts, trikes, punches and kicks; how to complement your karate training with sparring drills and kata; effective ways to succeed in karate-how to create a training program, test for belt promotion, and an overview of competitions and tournaments; resources to help you develop your knowledge and understanding of karate. Whether you're just getting started, or have already been training for a year of two, Karate Basics offers an easy, yet comprehensive introduction to the sport that will make you feel more confident and enable you to become successful much more quickly
Introduction -- Getting started -- Learning the basics -- Applying the basics -- The training session -- Making progress
Includes bibliographical references (p. 180-185)
Keywords: Karate